Educational Competitions of the Family Doctor in their Acting as Tutor in the Career of Medicine - José de la Caridad Lorenzo López; Beatriz María Fuster Cabrera; Belkis González Aguiar; Annia Machín Acia (Medisur)
Background: for the identification of a group of competitions characteristic of the educational work of the Family doctors that you/they act as tutors in the formative scenarios of the Primary Attention of Health in University Policlínico Cecilio Ruíz of Zárate. Objective: to identify the educational main competitions of the doctors of the family like tutors in the career of Medicine, in the Area II of the municipality of Cienfuegos. Method: pedagogic investigation of descriptive type in the mark of the medical education that looked for to define the group of educational basic competitions, what can favor a pedagogic management of more quality in the medical clinics as formative scenario of University Policlínico Cecilio Ruíz of Zárate during the year 2010. Results: 61,5% of our tutors has more than 10 years of medical formation; more than the half, their 73.1% is not categorized, 84.6% is specialist of general integral medicine, but of the half they received the preparation shop for tutors and 96.2% they consider the basic competitions as very important. Conclusion: deficiencies exist in the way of the tutor's performance for categorized personnel's lack, pedagogic scarce preparation and the assistance load of the professors in the primary attention of health.